Cyber-Physical Systems of Systems Foundations - A Conceptual Model and Some Derivations: The AMADEOS Legacy - Bondavalli, Andrea; Bouchenak, Sara; Kopetz, Hermann (Programming and Software Engineering, 2016)
Computer Systems Organization and Communication Networks; Software Engineering; Complex Systems; Information Systems Applications (incl. Internet); Computer Applications